Multivariate Analysis of UPLC-MS/MS Metabolomic Profiles in Four Hiraea Species (Malpighiaceae) - Jaqueline Munise Guimarães da Silva; Rafael Felipe de Almeida; Maria Luiza Zeraik (Separations, 2025)
The presence of bioactive compounds is reported in several Malpighiaceae species. However, little metabolomic information is documented in the genus Hiraea (Malpighiaceae). Thus, the objective was to identify secondary metabolites in the leaves of Hiraea cuiabensis, H. hatschbachii, H. reclinata, and H. restingae using ultra-performance liquid chromatography coupled to mass spectrometry (UPLC-MS/MS) and to compare the profiles by VIP score (partial least squares discriminant analysis, PLS-DA). Leaves were extracted with ethanol–water (4:1 v/v) and subjected to UPLC-MS/MS. The UPLC-MS/MS chromatographic profiles (in both positive and negative ionization modes) were separately processed and compared using the VIP score (PLS-DA). Fifty compounds were annotated, forty-five for the first time in the genus Hiraea, including flavonoids and phenolic acids, such as chlorogenic acid. The VIP score analysis revealed differences in the intensities of the compounds identified in Hiraea leaves (95% confidence), with rutin and myricitrin as the key metabolites for distinguishing among the four Hiraea species. These findings contributed to an understanding of the chemical diversity within Hiraea, suggesting possible ecological adaptations and potential pharmacological applications.